In vitro Evaluation of the Cytotoxicity of Chairside CAD/CAM Block Materials for Fabricating Dental Restorations - Sherif El Sayed Sultan; Mazen Anwar Abdullah Albadi; Faris Salah Alhassan; Sherif Magdy Elsharkawy (Wolters Kluwer Medknow Publications, 2024)
Background: The increasing utilization of chairside computer-aided design/computer-aided manufacturing (CAD/CAM) block materials in dentistry necessitates a comprehensive evaluation of their cytotoxicity to ensure patient safety. This study aimed to assess the cytotoxic effects of commonly used chairside CAD/CAM block materials for fabricating dental restorations. Materials and Methods: Several chairside CAD/CAM block materials including zirconia, lithium disilicate, and resin-based composites were evaluated for cytotoxicity using an in vitro model. Human gingival fibroblasts were cultured and exposed to extracts from each material. Cytotoxicity was assessed using MTT assay after 24, 48, and 72 hours of exposure. Additionally, cell morphology and viability were examined using microscopy. Results: The MTT assay revealed varying degrees of cytotoxicity among the tested materials. Zirconia demonstrated the least cytotoxicity with cell viability of 85% ± 5%, 82% ± 4%, and 79% ± 6% at 24, 48, and 72 hours, respectively. Lithium disilicate exhibited moderate cytotoxicity with cell viability of 70% ± 6%, 65% ± 7%, and 60% ± 5% at the corresponding time points. Resin-based composites displayed the highest cytotoxicity with cell viability of 55% ± 8%, 45% ± 6%, and 40% ± 4% at 24, 48, and 72 hours, respectively. Microscopic examination revealed altered cell morphology and reduced cell viability in the presence of resin-based composites. Conclusion: Chairside CAD/CAM block materials exhibit varying degrees of cytotoxicity, with zirconia demonstrating the least and resin-based composites showing the highest cytotoxic effects. These findings underscore the importance of considering cytotoxicity profiles when selecting CAD/CAM materials for dental restorations to ensure patient safety and biocompatibility.